2012
DOI: 10.1182/blood.v120.21.5168.5168
|View full text |Cite
|
Sign up to set email alerts
|

Study of Serum Hepcidin in Hereditary Hemolytic Anemias

Abstract: 5168 Background: Thalassemia is the most common genetic disorder in Egypt composes a major health problem with an estimated carrier rate of 5. 3%-9%. Registered cases in large centers in Egypt September 2007 were 9912 cases, and in Cairo University hematology clinic were alone 2597 cases. Patients with thalassemia major requiring regular blood transfusions accumulate iron that is toxic to the heart, liver, and endocrine systems. Hepcidin, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
3
0
3
Order By: Relevance
“…Based on the results in our study, the level of hepcidin in thalassemia group was higher than control group. This was in agreement with Origa et al [28], who found increased urinary hepcidin level in thalassemia major patients more than in control and in disagreement with Casanovas et al [29], and EL Beshlawy et al [30], who found that serum hepcidin levels are decreased in all patients of chronic hemolytic anemia, they suggested that the diseased erythron dysregulates iron homeostasis by inhibiting hepcidin synthesis, even in the presence of iron overload.…”
Section: Discussionsupporting
confidence: 84%
“…Based on the results in our study, the level of hepcidin in thalassemia group was higher than control group. This was in agreement with Origa et al [28], who found increased urinary hepcidin level in thalassemia major patients more than in control and in disagreement with Casanovas et al [29], and EL Beshlawy et al [30], who found that serum hepcidin levels are decreased in all patients of chronic hemolytic anemia, they suggested that the diseased erythron dysregulates iron homeostasis by inhibiting hepcidin synthesis, even in the presence of iron overload.…”
Section: Discussionsupporting
confidence: 84%
“…viral and autoimmune hepatitis) (14,15) and hematological disease (e.g. hereditary hemochromatosis and hereditary hemolytic anemia) (16,17).…”
mentioning
confidence: 99%
“…Além das hemocromatoses, outras doenças genéticas associadas com baixa produção de hepcidina são as anemias hemolíticas congênitas (talassemias, anemia falciforme, anemia sideroblástica, esferocitose hereditária, entre outras) (PASRICHA et al, 2013;BESHLAWY et al, 2012;KEARNEY et al, 2007). Embora as bases moleculares destas doenças não estejam diretamente relacionadas com a maquinaria de produção da hepcidina, muitas complicações destas síndromes hemolíticas são decorrentes da descompartimentalização corporal do ferro (GREER et al, 2009).…”
Section: Revisão Da Literaturaunclassified
“…Antigos estudos ferrocinéticos em pacientes com esferocitose hereditária indicam que a demanda diária do mineral aos tecidos hematopoiéticos pode ser até seis vezes maior (150 mg) do que a de indivíduos saudáveis (CONRAD & BARTON, 1981apud LATUNDE-DADA et al, 2006FINCH et al, 1970). Apesar de, nesta condição, as concentrações circulantes de hepcidina se mostrem inversa e fortemente relacionadas com a atividade eritropoética (BESHLAWY et al, 2012;KEARNEY et al, 2007), uma sobrecarga de ferro clinicamente importante não é ocorrência comum, a menos que transfusões de sangue sejam frequentes (ROCHA et al, 2011;LATUNDE-DADA et al, 2006;MEYRICK, WEBB & COLE, 2002).…”
Section: Revisão Da Literaturaunclassified
See 1 more Smart Citation